2018
DOI: 10.1126/scitranslmed.aam6354
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α 4 β 7 expression on peripheral blood CD4 + T cells predicts HIV acquisition and disease progression outcomes

Abstract: The gastrointestinal (GI) mucosa is central to HIV pathogenesis, and the integrin αβ promotes the homing of immune cells to this site, including those that serve as viral targets. Data from simian immunodeficiency virus (SIV) animal models suggest that αβ blockade provides prophylactic and therapeutic benefits. We show that pre-HIV infection frequencies of αβ peripheral blood CD4 T cells, independent of other T cell phenotypes and genital inflammation, were associated with increased rates of HIV acquisition in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
106
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(124 citation statements)
references
References 50 publications
16
106
2
Order By: Relevance
“…It is important to highlight that we were powered to detect increases or decreases equal to or greater than the ones shown in Supplemental Table 1, and it is possible that by using a larger sample size, one may detect smaller changes that were imperceptible here. Enhanced expression of α 4 β 7 integrin, a mucosal homing marker, has also been shown to contribute to susceptibility to HIV infection and to worsen HIV clinical prognosis (54). Further supporting a role for the integrin, α 4 β 7 blockade with a monoclonal antibody was recently shown to reduce HIV susceptibility and suppress viral load in NHPs (55,56).…”
Section: Discussionmentioning
confidence: 98%
“…It is important to highlight that we were powered to detect increases or decreases equal to or greater than the ones shown in Supplemental Table 1, and it is possible that by using a larger sample size, one may detect smaller changes that were imperceptible here. Enhanced expression of α 4 β 7 integrin, a mucosal homing marker, has also been shown to contribute to susceptibility to HIV infection and to worsen HIV clinical prognosis (54). Further supporting a role for the integrin, α 4 β 7 blockade with a monoclonal antibody was recently shown to reduce HIV susceptibility and suppress viral load in NHPs (55,56).…”
Section: Discussionmentioning
confidence: 98%
“…A growing body of evidence has demonstrated that α4β7 + CD4 + T cells represent an early target for HIV-1 (18,19,21). Accordingly, NHP studies utilizing an anti-α4β7 mAb, that is a close analogue of VDZ, either prior to infection, or in the context of SIV infected animals receiving cART, have yielded promising and provocative results (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lines of evidence demonstrate that α4β7-expressing cells represent early targets for the virus (16)(17)(18)(19)(20). This was highlighted in a recent report demonstrating that pre-infection frequencies of α4β7 on circulating CD4 + T cells may predict the risk of HIV-1 acquisition and disease progression independent of other T cell phenotypes and genital inflammation in a large cohort of at-risk South African women (21). Supporting this finding, STDs that have been linked with increased risk of HIV-1 acquisition, increase the frequency of α4β7 + CD4 + memory T cells in both the mucosa and blood (22,23).…”
Section: Introductionmentioning
confidence: 95%
“…The integrin α4β7 has been shown on a T cell subset that is highly susceptible to HIV-1 infection (Cicala et al, 2009;Sivro et al, 2018). Moreover, the integrin α4β1 was shown to be expressed by more than 70% of infected cells both in untreated and ART-suppressed individuals (Pardons et al, 2019).…”
Section: Markers Of Latently-infected Cd4 + T Cellsmentioning
confidence: 99%